Certainly of Divorce Laws in Different Countries Base on Indonesian International Civil Law - Devi, Ria Sintha (Journal of Progressive Law and Legal Studies, 2024)
Recognition and implementation of the divorce decision. Therefore, a thorough understanding of the principles of private international law is essential to navigate these complex legal challenges. Principles such as lex loci celebrationis, lex domicilii, and the principle of recognition and enforcement of foreign judgments serve as guidelines in handling inter-country divorce cases. Court jurisdiction, the choice of applicable law, and the process of recognizing and implementing divorce decisions between countries are important focal points in legal settlements. International divorce, especially involving spouses of different nationalities, raises a number of complex issues. From determining jurisdiction to choosing the applicable law, every step in the divorce process requires careful consideration. In this context, several international treaties, such as the Convention on the Civil Aspects of International Divorce, provide a uniform legal framework for dealing with such divorce cases. In addition, the importance of recognizing and enforcing foreign divorce judgments in other jurisdictions is an important factor in preventing multiple divorces and providing legal certainty. This process involves coordination between countries to respect and recognize foreign court decisions. Protecting children's rights in interstate divorce is an important focus, with jurisdictional determination and appropriate application of the law to ensure the child's best interests are safeguarded. An in-depth understanding of international private law, especially in the context of divorce from different countries, is the key to ensuring justice and legal certainty for all parties involved. In handling inter-country divorce cases in Indonesia, especially those involving couples with different nationalities, it is important to pay attention to national legal regulations, applicable laws and regulations, and guidelines from relevant international conventions. The divorce process in Indonesia, as explained in Article 66 of the Marriage Law, must follow the applicable national laws and regulations. This research, using normative juridical methods, provides in-depth insight into how international private law is applied in inter-state divorce cases in Indonesia. By exploring the principles of private international law and examining expert views, this research discusses the legal complexities involving marriage between countries and contributes to further understanding of legal certainty in this context. Overall, interstate divorce opens up a broad discussion of private international law issues, including jurisdiction, choice of law, recognition, and protection of children's rights. With increasing human mobility and globalization, a deep understanding of the principles of international private law is becoming increasingly important in dealing with marriages and divorces from different countries.